Experimental Characterization of NURSE, a Device for Arm Motion Guidance - Betsy Dayana Marcela Chaparro Rico (Journal of Healthcare Engineering, 2018)
This paper presents an experimental characterization of NURSE, a device for arm motion guidance. The laboratory setup and testing modes are presented to explain the experimental procedure. Two exercises for the upper limb exercise are used to test the NURSE behaviour, and successful results are presented. Trajectories and linear accelerations are tested when the device performs the two exercises without and with load. In addition, torque and power consumption are considered to check the NURSE behaviour.